Propaganda and Zionist education : the Jewish National Fund, 1924-1947 - Bar-Gal, Yoram (University of Rochester Press, 2003)
The Jewish National Fund (JNF) is the executive body established by the Zionist movement in 1902 to buy land in Palestine for the Jewish people. Very quickly, however, it became an international organization and soon had branches in many countries through.